Pengembangan Media Pembelajaran Pai Berbasis Teknologi Untuk Meningkatkan Keterampilan Siswa Di Sekolah Dasar Negeri 3 Kampung Baru Kota Bandar Lampung - Muhammad Al Imron; Ilham Fathoni; Misalia Sari; Maylia Khairunnisa Baher; Agus Jatmiko (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This research aims to develop technology-based Islamic Religious Education (PAI) learning media to enhance students' skills at State Elementary School 3 Kampung Baru, Bandar Lampung City. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection was carried out through observation, interviews, questionnaires, and student skill tests. The research results show that the technology-based learning media developed is effective in improving students' understanding and skills in the subject of PAI. The main findings include: (1) a significant increase in the average student scores by 25% after using the media, (2) positive responses from teachers and students regarding the ease of use of the media, and (3) an increase in student learning motivation. The implications of this research highlight the importance of integrating technology into Islamic Religious Education (PAI) to create a more interactive and engaging learning experience. In addition, the findings provide practical contributions for teachers in designing innovative learning strategies that meet the needs of 21st-century students. This research also offers recommendations for schools and educational policymakers to support the availability of adequate technological facilities as well as continuous training for teachers to enhance their digital competence. Thus, the integration of technology in PAI not only functions as a learning aid but also as a means to foster 21st-century skills such as digital literacy, critical thinking, collaboration, and effective communication among students.